Analysis of the achievements strategies and their economic impact from Carlos Slim-Helu in the Telecommunications industry - Gutiérrez-Rentería, María Elena (2022)
Some Mexican companies have stood out as leaders in the Latin American Telecommunications market. The offer has helped to society, characterized by spend or invest more time in the digital media and Mobile phones, to the detriment of consumption of traditional media. This research describes the strategic and competitive participation of Carlos Slim-Helu since 1990. The employer took advantage of the opportunities presented by digital technologies, and, also, the convergence between Telecommunications and Media industries. At present, he has influence in 18 countries in Latin America. The study shows the economic results of America Movil in 2010. The Mobile phone and triple play business contribute to economic and social profitability of the company.